2023
DOI: 10.3390/healthcare11101498
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality for Upper Extremity Rehabilitation—A Prospective Pilot Study

Pinar Tokgöz,
Dirk Wähnert,
Andreas Elsner
et al.

Abstract: Applications related to virtual reality are a rapidly growing area. Thus, these technologies are also increasingly used in the field of medicine and rehabilitation. The primary objective of this prospective pilot study was to investigate the feasibility, user experience and acceptance of a virtual-reality-based system for upper extremity rehabilitation. The study was conducted as a single-center trial over 16 weeks. The eligibility criteria included rehabilitants with upper extremity injuries of at least 18 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…In addition, a previous study concluded that immersive VR using an interactive kitchen environment provided better improvement in upper limb functional activities and pain in patients with upper limb complex regional pain syndrome [14]. Another study revealed that Meta Quest 2 VR based rehabilitation using three different tasks (1 st memory game matching button pairs, 2 nd drawing a threedimensional trajectory between highlighted planets to connect them, and 3 rd touching pairs of hands (left and right) from their respective sides) significantly improved upper limb function and shoulder and elbow joint mobility in their study for upper limb injuries [15]. Similar results were obtained for both upper limb functional performance and pain in patients with subacromial impingement syndrome [16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous study concluded that immersive VR using an interactive kitchen environment provided better improvement in upper limb functional activities and pain in patients with upper limb complex regional pain syndrome [14]. Another study revealed that Meta Quest 2 VR based rehabilitation using three different tasks (1 st memory game matching button pairs, 2 nd drawing a threedimensional trajectory between highlighted planets to connect them, and 3 rd touching pairs of hands (left and right) from their respective sides) significantly improved upper limb function and shoulder and elbow joint mobility in their study for upper limb injuries [15]. Similar results were obtained for both upper limb functional performance and pain in patients with subacromial impingement syndrome [16].…”
Section: Discussionmentioning
confidence: 99%
“…Later, VR appeared in applications aimed at adults. VR applications have been used in the treatment/rehabilitation of orthopedic conditions (such as ankle sprains and shoulder pain and impingement) [19], neurological rehabilitation [20], the general rehabilitation of the upper body, particularly the upper extremities [21,22], Parkinson's disease, Alzheimer's disease, and eating disorders [23]. Many studies show the effectiveness of VR in neurological rehabilitation [24][25][26][27], including post-stroke rehabilitation [15,26,28].…”
Section: Introductionmentioning
confidence: 99%